THE EFFECTIVENESS OF QUORA APPLICATION TO IMPROVE STUDENTS’ READING SKILL - Irwan, Anis Lisdayanti; Nur Qalbi; Muh Arief Muhsin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2020)
This research aimed to find out the effectiveness of quora application to the students’ reading comprehension in terms of main idea and conclusion at XI IPA 2 of SMA Negeri 2 Takalar. The method in this research, the researcher used a pre-experimental research which XI IPA 2 SMA Negeri 2 Takalar with the number of the subject 30 students. Instrument of this research is reading test. The result of the data indicated that there was difference between students pre-test and post-test. The mean score of post-test of the students’ reading comprehension was greater than pre-test in term main idea (5.4>3.06) and in term (4.6>2.73). From t-test researcher found, the value of t-test was greater that t-table (6.115>1.699) at the level of significance 0.05 with degree of freedom (df) = 29, it means that there was significant difference between students’ comprehension before and after using Quora application. It is also said that the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. The result of the research, Quora application was effective in improving students’ reading comprehension.